Lung function measures following simulated wildland firefighter exposures. Issue 9 (2nd September 2017) - Ferguson, Matthew D.; Semmens, Erin O.; Weiler, Emily; Domitrovich, Joe; French, Mary; Migliaccio, Christopher; Palmer, Charles; Dumke, Charles; Ward, Tony
ABSTRACT: Across the world, biomass smoke is a major source of air pollution and is linked with a variety of adverse health effects. This is particularly true in the western U.S. where wood smoke from wildland forest fires are a significant source of PM2.5 . Wildland firefighters are impacted as they experience elevated PM2.5 concentrations over extended periods of time, often occurring during physical exertion. Various epidemiological studies have investigated wood smoke impacts on human health, including occupational field exposures experienced by wildland firefighters. As there are numerous challenges in carrying out these field studies, having the ability to research the potential health impacts to this occupational cohort in a controlled setting would provide important information that could be translated to the field setting. To this end, we have carried out a simulated wildland firefighter exposure study in a wood smoke inhalation facility. Utilizing a randomized crossover trial design, we exposed 10 participants once to clean filtered-air, 250 µg/m 3, and 500 µg/m 3 wood stove-generated wood smoke PM2.5 . Participants exercised on a treadmill at an absolute intensity designed to simulate wildland firefighting for 1.5 hr. In addition to measured PM2.5 smoke concentrations, mean levels of CO2, CO, and % relative humidity were continuously monitored and recorded and were representative of occupational "real-world" exposures. Pulmonary function was measured at three time points: before, immediately after, and 1-hr post-exposure. Although there were some reductions in FVC, FEV1, and FVC:FEV1 measures, results of the spirometry testing did not show significant changes in lung function. The development of this wood smoke inhalational facility provides a platform to further address unique research questions related to wood smoke exposures and associated adverse health effects.